Utilization of low rank coal as oxidation catalyst by controllable removal of its carbonaceous component - Nurhadi, Mukhamad (Taiwan Institute of Chemical Engineers, 2015)
Controlled removal of carbonaceous component in low rank coal by sulfonation followed by calcination demonstrated that it is a simple and effective method to utilize this material as catalyst in the oxidation of styrene. Low rank coal is one of the least utilized categories of coal. However, it shows excellent potential as a catalyst due to high concentrations of carbon and other elements, such as transition metals, which are embedded inside its structure. In this research, the low rank coal was treated by sulfonation followed by calcination in order to activate the transition metals embedded in it. The catalytic activity of the treated low rank coal was tested in the oxidation of styrene by aqueous hydrogen peroxide. The low rank coal showed high catalytic activity after sulfonation and calcination at 700. °C, with 3% of styrene conversion and 97% of selectivity toward benzaldehyde. The transition metal active sites in low rank coal that play the most important role in the oxidation of styrene were determined by coal mimicking models. The presence of cobalt oxide and titanium oxide active sites in the low rank coal plays the most significant role in the oxidation of styrene by aqueous hydrogen peroxide.